Retraction: Stein, J.A. et al. The Effects of Acute Caffeine Supplementation on Performance in Trained CrossFit Athletes. Sports 2019, 7, 95 - Jesse A. Stein; Melitza Ramirez; Katie M. Heinrich (Sports, 2020)
All authors of the published article [...]